2007
DOI: 10.1007/s11269-007-9154-3
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of New Irrigation Technology Under Production Risk

Abstract: This paper investigates the factors affecting adoption of new irrigation technologies and also addresses the linkage between this type of technology and production risk. The risk-premium associated with the use of water is estimated by adapting a momentbased approach. Farm-level data were collected from a sample of 187 wheat farms, located in the three major districts of Fars province of Iran during the years 2002 and 2003. Results of this study demonstrate that the risk premium decrease with new irrigation te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…However, modern irrigation technology is also recognized for being a risk-decreasing input when reducing dependence on rainfall and water availability, which make yields more stable. Koundouri et al (2006) and Torkamani and Shajari (2008) found a positive effect of production risk on switching from traditional to modern irrigation technology, supporting a riskdecreasing effect.…”
Section: Conceptual Framework On Adoption Of New Technologymentioning
confidence: 83%
See 1 more Smart Citation
“…However, modern irrigation technology is also recognized for being a risk-decreasing input when reducing dependence on rainfall and water availability, which make yields more stable. Koundouri et al (2006) and Torkamani and Shajari (2008) found a positive effect of production risk on switching from traditional to modern irrigation technology, supporting a riskdecreasing effect.…”
Section: Conceptual Framework On Adoption Of New Technologymentioning
confidence: 83%
“…Even though literature on adoption of modern irrigation technology is well-documented, there is little evidence concerning production risk and irrigation choices. Two exceptions are Koundouri et al (2006) and Torkamani and Shajari (2008). Both studies find support of a positive and significant effect of production risk on adoption decisions, arguing that new irrigation technology is a risk-decreasing input.…”
Section: Introductionmentioning
confidence: 94%
“…Farmers in rainfed and partially irrigated settings can reduce the variance and increase the mean of their crop yields by investing in measures that modify soil moisture availability [36,37]. Farmers who capture rainwater in a small pond for irrigation, or pump groundwater from a shallow aquifer, can manage the amount of soil moisture available during crop growth and reproductive stages.…”
Section: Estimates Of Water Productivity Are Random Variablesmentioning
confidence: 99%
“…While downside risk aversion is integrated in several economic studies that show its relevance for decision making processes of farmers (e.g. Koundouri et al, 2006;Torkamani and Shajari, 2008;Groom et al, 2008), to our knowledge, no attempts have been made to augment integrated bio-economic models addressing agricultural water use by accounting for farmers' downside risk aversion. This article contributes filling this gap by presenting a straightforward integration of downside risk and downside risk aversion in a bioeconomic model.…”
Section: Introductionmentioning
confidence: 99%